Profil Kemampuan Komunikasi Matematis Siswa SMP Kelas VII Al Faqihil Muqoddam - Fitriya, Zahrotul; Suriyana, Suriyana; Nizarrahmadi, Nizarrahmadi (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to describe the mathematical communication skills of seventh-grade students at Al-Faqihil Muqoddam Junior High School in social arithmetic. The type of research used is descriptive qualitative research. The research subjects consisted of 10 seventh-grade students in the even semester of the 2024/2025 academic year. Data were collected through tests and interviews. The test instrument consisted of three essay questions designed to measure students' mathematical communication skills, while interviews were used to deepen understanding of the test results. The results of the study showed that most students were able to meet the indicators of mathematical communication skills, such as writing mathematical ideas clearly, using symbols or representations appropriately, and explaining the steps to solve problems logically. Thus, it can be concluded that the students' mathematical communication skills in social arithmetic are good and effective